PENGARUH DUKUNGAN PEMBEKALAN PANGKALAN TNI ANGKATAN LAUT TERHADAP OPERASI PENGAMANAN PERBATASAN - Constantius Rusmaji; Edi Suhardono (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2019)
This study explains the support variables for Naval Base supplies for border security operations. The research method used is a quantitative method by distributing questionnaire.The number of samples taken was 80 samples from the total population of 371 persons. The research was carried out starting from the classification of samples respondents based on gender, age, education and years of service. The research variables in this study are supporting variables in the supply as independent variables (X) and border security operations variables as cooperation variables (Y). Indicators for variable X include: personnel involved in the supply, infrastructure for the supply of equipment, supporting facilities for the supplies and types of supplies that can be supported. While indicators on the Y variables include: personnel involved in the operation, operating facilities, area of ​​operation and duration of operation. The data analysis process is carried out with several tests, among others: validity test, namely testing the data analysis process to determine whether the research instrument is valid or not. The next test is the reliability test, the data analysis process to answer the accuracy of the research instruments. The normality of the trial is tested. The next data analysis process is the hypothesis test in the regression test. Regression test is a process of analyzing data to study the influence between research variables. The regression test conducted in this study is a partial regression test because the independent variable used is one variable. After it was implemented, everything was proven. Supports provisioning variables. Naval Base determines positive and significant impact on border security operations.